Pengaruh Disiplin Dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai Pada Balai Besar Meteorologi Klimatologi Dan Geofisika (MKG) Wilayah II Tangerang Selatan - Nindia Oktavia Nurhidayah; Indri Indirasari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study is motivated by the decline in employee performance at the Center for Meteorology, Climatology, and Geophysics (MKG) Region II South Tangerang, which is presumed to be caused by inadequate work discipline and suboptimal physical work environment conditions. The purpose of this research is to analyze the partial and simultaneous influence of work discipline and physical work environment on employee performance. This research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to 80 employees selected by purposive sampling. The data were analyzed using multiple linear regression with SPSS software. The results indicate that both work discipline (X1) and physical work environment (X2) have a positive and significant effect on employee performance (Y). Partially, work discipline shows a t-value of 2.538 > t-table 1.1665 with a significance level of 0.000 < 0.05, while the physical work environment shows a t-value of 11.425 > t-table 1.991 with a significance level of 0.000 < 0.05. Simultaneously, both independent variables significantly affect employee performance, with an F-value of 3.443 > F-table 2.723 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) is 0.25, indicating that 25% of the variance in employee performance is explained by work discipline and the physical work environment. This study recommends improving discipline through consistent supervision and enforcement of sanctions, as well as enhancing physical work facilities to support optimal employee performance Keywords: Discipline; Physical Work Environment; Employee Performance.